2013
DOI: 10.5114/fn.2013.34194
|View full text |Cite
|
Sign up to set email alerts
|

Original article High resolution proton nuclear magnetic resonance (1H NMR) spectroscopy of surviving C6 glioma cells after X-ray irradiation

Abstract: A b s t r a c t (24, 48, 72 and 96 hours) P Pu ur rp po os se e: : To study biochemical response of living model of glioma to X-rays irradiation using high resolution proton nuclear magnetic resonance ( 1 H NMR) spectroscopy. M Ma at te er ri ia al l a an nd d m me et th ho od ds s: : Rat glioma C6 cells were irradiated with 3.8 Gy (D 0 , the 37% clonogenic survival dose) of X-rays from a teletherapy unit at the dose rate 8.8 Gy/min. After irradiation the cells were incubated at 37°C/5%CO 2 /95%O 2 for vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…Following treatment with antitumor glycosides, an increase in free choline and PC was reported in C6 glioma tumors in mice, suggesting that the mode of action of glycosides involves alterations in phospholipid metabolism resulting in cell death . X‐ray irradiation as well as treatments with the nitrones PBN and OKN007, both induced a significant decrease in the level of lipids related to the modulation of extent of necrosis .…”
Section: Preclinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Following treatment with antitumor glycosides, an increase in free choline and PC was reported in C6 glioma tumors in mice, suggesting that the mode of action of glycosides involves alterations in phospholipid metabolism resulting in cell death . X‐ray irradiation as well as treatments with the nitrones PBN and OKN007, both induced a significant decrease in the level of lipids related to the modulation of extent of necrosis .…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…Response to multiple therapeutic approaches has been evaluated in preclinical in vivo models of GBM using 1 H MRS . Among these, treatment with the phosphatidylinositol‐3‐kinase (PI3K) irreversible inhibitor, PX‐886, resulted in a decrease in the MRS‐detectable Cho‐to‐NAA ratio, which was linked to increased autophagy post‐treatment .…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…The CH 2 /CH 3 ratio increased from 1.25 (non-irradiated cells) to 1.61 (irradiated cells). Increase in the lipid signals, especially increase in CH 2 / CH 3 ratio, is frequently claimed to be associated with progression of apoptotic death (Santini et al, 2006a;Santini et al, 2006b;Rainaldi et al, 2008;Matulewicz et al, 2013) and with disruption of fatty acid metabolism (Goudarzi et al, 2014). Blankenberg et al (Blankenberg et al, 1997) observed that in lymphoblasts treated with doxorubicin the onset of apoptosis was accompanied by over twofold increase in the CH 2 resonance.…”
Section: Discussionmentioning
confidence: 99%